Insights into Effective Labeling Strategies for Homeopathic Products (Homoeopathy for All, 2024)
Even in this age of heightened  consumer consciousness, the health  care industry remains a source of  concern. This is particularly true  regarding the extent and quality of  information provided to patients  and health professionals by the  pharmaceutical industry. Labeling  medicines in India is an important  aspect of ensuring patient safety  and compliance with regulatory  requirements. The label of over-the counter (OTC) medicines plays a  crucial role in conveying valuable  information to the patient for safe  and effective use. A survey of the  labeling information provided for  Ayush drugs, especially ayurvedic  drugs, marketed in India highlights  the importance of accurate and  clear labeling for these traditional  medicines. Correct drug labeling  is central for ensuring proper drug  dispensing and thus for patient  safety. Labeling errors may result  in adverse health outcomes. A  study by Shah el al show highlights  the lacunae in the contents of the  labeling of drugs and recommends  strict enforcement of Drugs Act for  better and safer use of medicines.
Keywords: Insights; Homeopathic